VALIDASI METODA FRAP MODIFIKASI PADA PENENTUAN KANDUNGAN ANTIOKSIDAN TOTAL DALAM SAMPEL MANGGA DAN RAMBUTAN - -, Yefrida; Ashikin, Nor; -, Refilda (Universitas Andalas, 2015)
Validation of modified FRAP method to determine total antioxidant content in mango and rambutan sample have been done. Total antioxidan content in sampel is presented as Gallic Acid Equivalent (GAE). Modified FRAP method using FeCl3asoxidizing agent and ortho-phenantroline as complexan, which produce complex compounds of [Fe (C12H8N2)3]+2 sorrel coloured. Validation parameters are obtained in this research are r = 0.999, R2 = 0.998, LoD 3.13 x 10-6 M and LoQ 1.04 x 10-5 M. While RSD and recovery in the sample mango and rambutan were 1.15%, 1.34% and 96.31%, 97.72%, respectively. Based on the value of the validation parameters, it can be concluded that this method can be used for determination of total antioxidant content in the mango and rambutan samples.